Keterkaitan antara Kualitas Pelayanan, Kepuasan Pelanggan dan Retensi Pelanggan di Sektor Perbankan - Eka Tirtawati, Desak Gede (Program Studi Manajemen, 2021)
Customer retention is one of the key indicators in the service industry. One of the ways to increase customer retention is by improving service quality and customer satisfaction. This study was conducted to understand about correlation between customer satisfaction and customer retention in the B2C market. This study examined the effect of service quality and customer satisfaction on retention in the banking sector, as these variables had not been tested simultaneously before. This study used Structural Equation Modeling (SEM) to analyze 150 samples from customers of Bank Central Asia (BCA) in Jakarta. The questionnaire have been distributed to respondents who have been selected through technique sampling purposive. The result showed that service quality give positive impact on customer satisfaction and customer retention in Bank BCA.